Surveillance of influenza A H1N1 2009 among school children during 2009 and 2010 in São Paulo, Brazil - Guatura,Sandra Baltazar (2012)
INTRODUCTION: Influenza A H1N1 2009 is associated with a high morbidity rate among children around the world, including Brazil. This survey was conducted on samples of symptomatic children (< 12 years) to investigate the influenza virus as the etiological agent of respiratory infections in a day care school in a health facility during the first and second pandemic wave of H1N1 (2009-2010) in São Paulo, Brazil. METHODS: Influenza infections were determined by real-time PCR in 34% (47/137) of children with a median age of 5 years (8 months - 12 years), from June to October 2009 and in 16% (14/85) of those with median age of 6 years (1-12 years), from March to November 2010. RESULTS: In general, most positive cases (64%) occurred in children aged 5-12 years, this age group was significantly the most affected (39.8%, p = 0.001, OR = 8.3, CI 95% 1.9-36.9). Wheezing was reported by 31% (19/61) and dyspnea by 23% (14/61) of the studied patients. An outbreak of influenza H1N1 with an attack rate of 35.7% among children (median age 6 years) was documented in April 2010, before the vaccination campaign against the pandemic virus was extended for children up to 5 years in Brazil. CONCLUSIONS: Therefore, the study reinforces the recommendation to immunize school children to reduce the incidence of the disease.